(untitled) (Journal of Research Updates in Polymer Science, 2025)
Hybrid composites have been considered emerging materials that have garnered the attention of researchers around the globe. Combining two kinds of reinforcement may balance their merits and demerits in hybrid composites. In this work, glass fiber/wire mesh-reinforced epoxy composites were prepared via vacuum infusion to minimize void formation. Non-hybrid wire mesh and glass fiber-reinforced composites were also fabricated for comparison purposes. The thicknesses of all the composite laminates were fixed at 4 mm. Tensile tests were performed at a cross-head displacement rate of 2 mm/min with reference to ASTM D3039 to obtain the modulus of composite laminates. Subsequently, the tensile modulus of each composite laminate was predicted using the Rule of Hybrid Mixtures (RoHM). A comparison was made between the modulus of the composite laminates obtained from the tensile tests and prediction using RoHM. In accordance with the results obtained, it was found that the incorporation of glass fiber increased the modulus of the hybrid composites but did not significantly improve their tensile strength. The highest modulus (22.6 GPa) was obtained in non-hybrid glass fiber-reinforced composites, which is 107.71 % greater than non-hybrid wire mesh-reinforced composites. When comparing the experimental and predicted tensile modulus of the glass fiber/wire mesh composite laminates, both results matched well, demonstrating a linear increase in the tensile modulus with an increase in glass fiber content. Overall, the percentage error of the prediction was in the range of 3 – 6 %, indicating a high accuracy of the RoHM.